THE EFFECT OF COMMUNICATIVE AND AUDIO LINGUAL METHOD ON STUDENT’S CONVERSATIONAL ACHIEVEMENT - Ika Rebeka Tambunan; Elia Masa Gintings (State University of Medan, 2012)
The objective of this study was to discover the significant effect of student’s conversation when the student’s were taught by using Directed Communicative and Audio Lingual Method. The subjects of the study were one hundred and twenty students of State Senior High School Rantau Selatan, Labuhan Batu. The techniques of data analysis applied were quantitative and qualitative. In analyzing the data, the student’s were given three conversation assessments namely. It was found that the application of Directed Conversation thinking activity significantly the effect of communicative and audio lingual method on student’s achievement conversation. Key words: Communicative and Audio lingual method; Conversation